2003
DOI: 10.1159/000072070
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Levels of 8-Methoxypsoralen following Bath Water Delivery in Dermatological Patients

Abstract: With respect to the clinical advantages known for bath PUVA therapy, it was of interest to compare the plasma levels of 8-methoxypsoralen (8-MOP) in bath therapy with those after oral administration for a better insight into the pharmacokinetics of 8-MOP following different modes of application. Considerable high plasma levels of 8-MOP were observed after bath therapy with interindividual variability. The half-life of plasma 8-MOP was markedly shorter after bath PUVA than after oral application. The pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Higher concentrations of methoxsalen may result in a better therapeutic benefit, but these concentrations bear the risk of systemic resorption of methoxsalen and therefore of systemic adverse effects. 37 The mode of action of saltwater balneophototherapy is still subject to research. It has been shown that the photosensitivity to UV-B is markedly increased (lower MED) after exposure to tap-water or saltwater baths, but no concentration-dependent effect was found.…”
Section: Commentmentioning
confidence: 99%
“…Higher concentrations of methoxsalen may result in a better therapeutic benefit, but these concentrations bear the risk of systemic resorption of methoxsalen and therefore of systemic adverse effects. 37 The mode of action of saltwater balneophototherapy is still subject to research. It has been shown that the photosensitivity to UV-B is markedly increased (lower MED) after exposure to tap-water or saltwater baths, but no concentration-dependent effect was found.…”
Section: Commentmentioning
confidence: 99%
“…The mobile phase consisted of a mixture of methanol, acetonitrile and water (2:30:68) and the flow rate was 1ml/min (Monbaliu et al, 1981, Kappes et al, 2003). The linearity range was between 10-1000ng/ml ( R 2 = 0.99).…”
Section: Methodsmentioning
confidence: 99%
“…Patients take a warm bath with 0.5 -1.0 mg/l 8 - MOP for 20 min before they are exposed to UVA [ 18 ][ 19 ].…”
Section: Phototherapiesmentioning
confidence: 99%
“…For example, many studies show how nb-UVB combined with different topical drugs (e.g. Corticosteroids, vitamin D analogues, tacrolimus, pimecrolimus, pseudocatalase) could be more efficacy than phototherapy alone [ 16 ][ 17 ][ 18 ][ 19 ][ 20 ] [ 21 ][ 22 ][ 23 ][ 24 ]. In case of a combination, both TCI and vitamin D analogues should be used after UVB, never before to avoid risks such as hyperpigmentation or skin cancer.…”
Section: Phototherapiesmentioning
confidence: 99%